A comprehensive review of Pseudoperonospora cubensis: biology, epidemiology, and disease management - Kikway, Isaack; Keinath, Anthony P.; Ojiambo, Peter S. (Frontiers in Horticulture, 2025)
Over the past two decades, significant changes in the population structure of Pseudoperonospora cubensis have been reported worldwide. These changes have been associated with, among other things, severe epidemics of cucurbit downy mildew that are now much more destructive particularly on cucumber, than has previously been reported. Host specificity has complicated disease control as host resistance and fungicides that were previously effective in controlling the disease have become less effective. In response to this resurgence, significant research efforts have been made to better understand disease epidemiology, pathogen biology and host resistance, to generate information to improve disease management. Oospores have been reported under natural field settings in the United States, however, uncertainty remains regarding their role as a source of inoculum for initial disease outbreaks in northern latitudes that experience hard frost. Further, recent work indicates that the initial source of inoculum in the continental United States is southern Florida and along the edge of the Gulf of Mexico. Network analysis of disease outbreaks has identified key locations in the eastern United States that could be critical for disease monitoring in an effort to limit epidemic spread during the growing season. Lineage-specific biosurveillance of P. cubensis using spore traps complements existing disease monitoring efforts and is providing opportunities for precision management by determining cucurbit crops at risk of infection during the season. This review summarizes the substantial progress that has been made in understanding the biology of P. cubensis, disease epidemiology and control, which could inform better the management of cucurbit downy mildew.